Reliability and Assurance as Key Drivers of Luxury Hotel Guest Satisfaction: A Study from Sofitel Bali Nusa Dua - Desak Putu Ratmi Aryani (Depertment of Hospitality, Politeknik Pariwisata NHI Bandung, 2025)
Purpose of the study: This study aims to examine how service quality influences guest satisfaction at Sofitel Bali Nusa Dua, it seeks to identify which SERVQUAL dimensions most strongly affect satisfaction, providing evidence to support strategies for improving loyalty and occupancy in luxury hotel settings. Design/methodology: A quantitative survey using structured questionnaires was administered to 100 guests. Data were analyzed with SPSS software, employing validity and reliability tests, classical assumption checks, multiple linear regression, t-tests, F-tests, and R² based on the SERVQUAL framework. Findings: Service quality positively and significantly impacts guest satisfaction. Reliability and assurance are the dominant SERVQUAL dimensions, explaining 64.2% of satisfaction variance, while tangibles, responsiveness, and empathy show lesser effects. Research limitations/Implications: Results apply to luxury hospitality in Bali and similar resort destinations, aiding hotel management, guest experience design, and strategic planning in hospitality, tourism, and service marketing disciplines. Novelty/Originality of the study: This study offers hotel-specific evidence on SERVQUAL’s reliability and assurance as primary satisfaction drivers in post-pandemic luxury settings, advancing practical knowledge for targeted service enhancements in high-end hospitality.